Pemodelan Data Relasional pada NoSQL Berorientasi Dokumen - Muhammad Riza Alifi; Transmissia Semiawan; Djoko C.U. Lieharyani; Hashri Hayati (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2022)
Data management technology that continues to develop and boost the popularity of document-based not only structured query language (NoSQL) has become the most-used data model. Behind its popularity, data management technology offers an intriguing advantage, namely flexible data storage, whether in terms of data forms and sizes or structured and unstructured data. However, this data modeling flexibility has its challenge due to its impact on more complex scheme creations, without being accompanied by any need-based design patterns. This study aims to model relational data on the document-based NoSQL at its conceptual, logical, and physical levels. The conceptual design was developed based on processes, rules, and business requirements. The logical and physical designs were developed based on the extended references and computed design patterns determined from the operating workload. The relational data model design on the document-based NoSQL was successfully formed using the entity relationship diagram (ERD) with Chen notation for the conceptual, and collection relationship diagram (CRD) for both logical and physical levels. The conceptual design focused on the representation of entities, attributes, and relationships. Unlike the conceptual design which tends to be abstract, the focus of the logical design is on the collection schema (embedded and reference) representation, including design patterns influenced by the formation of relationships. Furthermore, the focus of physical level design is to represent the schema in a more concrete form. The physical design is almost the same as the logical one, the difference lies only in the detail addition for data types and structures. The evaluation of data model designs was also carried out for each level. This study contributes to designing a data model with the advantage of read-intensive capability since a joint operation among collections is not required and the computation process recurrence for derivative attributes is not necessary.